Antitumor Molecular Mechanism of Chlorogenic Acid on Inducting Genes GSK-3β and APC and Inhibiting Gene β-Catenin. (16th June 2013) - Xu, Ruoshi; Kang, Qiumei; Ren, Jie; Li, Zukun; Xu, Xiaoping
Abstract : Objective. Inhibiting gene β -catenin and inducting genes GSK-3 β and APC, promoting the tumor cell apoptosis in Wnt pathway, by chlorogenic acid were discussed (CGA). Method. The different genes were scanned by the 4*44K mouse microarray chips. The effect of the three genes was confirmed by RT-PCR technique with CGA dosage of 5, 10, and 20 mg/kg. Result. The expression of GSK-3 β and APC was upregulated in group of 20 mg/kg dosage (P < 0.05 ) and the expression of β -catenin was downregulated in the same dosage (P < 0.05 ). Conclusion. The results infer that the multimeric protein complex of β -catenin could be increased by CGA upregulated genes GSK-3 β and APC, which could inhibit the free β -catenin into the nucleus to connect with TCF. So the transcriptional expression of the target genes will be cut to abnormal cell proliferation. It is probably one of the ways that can stop the tumor increase by CGA.